Development of optical switch for indoor LAN using SMA coil and magnetic latch - Bhuiyan, Moinul; Haga, Yoichi; Makishi, Wataru; Esashi, Masayoshi (2003)
In case of indoor LAN (Local Area Network) for example in-home or office networks, plastic optical fiber (POF) is more suitable than the quartz optical fiber because of its flexibility and ease of connection by relatively large core diameter. 1×2 optical switch for indoor LAN using POF has been developed. For switching by movement of a POF, large displacement is needed because of large core diameter (for example, 0.486mm). Shape memory alloy (SMA) coil actuator is used for large displacement. A magnetic latch system is used for fixing the position of the displaced POF. Switching speed is less than 1 second and the loss of the fabricated switch is less than1 [dB].